Investigating The Rate of Pregnancy Success after Endometriosis Surgery in Infertile Patients with Advanced Endometriosis: A Retrospective Study - Zahra Asgari; Nasrin Hjiloo; Reihaneh Hosseini; Ashraf Moini; Zahra Valian; Samira Mirzaei; Nahid Rezaei Aliabadi; Lida Garrosi (International Journal of Fertility and Sterility)
Background: This study aims to determine the effect of laparoscopic surgery for advanced endometriosis on spontaneous pregnancy rates and assisted reproductive techniques (ARTs) in patients with endometriosis.Materials and Methods: This retrospective case series study included 74 reproductive-aged patients who were diagnosed with deep infiltrating endometriosis (DIE), desired to conceive, and underwent resection surgery at the Arash Women’s Hospital, Tehran, Iran between March 2017 and March 2021. Patients with any plausible infertility factors or abnormalities in their partner's semen analysis were excluded. At least 6 months after surgery, the patients were contacted by phone to evaluate the success rate of pregnancy in patients and by which approach they were convinced, i.e., naturally, ovulation induction, or using ARTs. Besides, the impact of patients’s factors on pregnancy success was evaluated.Results: During 3 years after surgery, 37 patients (50%) became pregnant. Out of the 37 pregnancies, 16 patients (43.2%) conceived spontaneously, while 21 patients (56.8%) used ARTs.The mean age of women who became pregnant was significantly lower than those who did not conceive. These two groups do not show any significant differences in terms of endometriosis stage, the maximum size of the cyst, DIE nodule type, and the number and anatomical places of nodules. Additionally, patients who benefit from ART are more likely to have adenomyosis. Conclusion: DIE surgery is associated with a considerable fertility rate. It is also important to note that patient age plays a significant role in the pregnancy rate of this population. Further randomized clinical trials are required to validate the obtained results.